Post Cholecystectomy Syndrome in a Patient due to Multiple Biliary Pathologies. - Thapa, Bikash Bikram; Shah, Kunda Bikram; Rawal, Sushil Bahadur; Malla, Srijan (Medical Journal of Shree Birendra Hospital, 2013)
Postcholecystectomy syndrome is the recurrence of symptoms after cholecystectomy. Postcholecystectomy syndrome due to a combination of cystic duct stump calculus and choledochal cyst with recurrent choledocholithiasis is a rare presentation. This is a case report of a patient who had developed recurrent common bile duct calculi despite endoscopic removal and eventully managed with Rou-en-Y Hepati cojejunostomy for having choledochal cyst 39 years postcholecstectomy. Medical Journal of Shree Birendra Hospital; Jan-June 2012/vol.11/Issue1/52-54 DOI: http://dx.doi.org/10.3126/mjsbh.v11i1.7792